Factors affecting compliance and health-seeking behaviour of hypertensive patients: a mixed-method study - Bhavna Bharatkumar Baria; Mohmmedirfan Hanifbhai Momin (International Journal Of Community Medicine And Public Health, 2026)
Background: Hypertension is a leading modifiable risk factor for cardiovascular morbidity and mortality worldwide. Despite availability of effective pharmacological and lifestyle interventions, optimal blood pressure control remains suboptimal, largely due to poor treatment compliance and delayed or inappropriate health-seeking behaviour. Objectives were to assess the extent of treatment compliance among hypertensive patients; to identify determinants of antihypertensive treatment compliance; to explore factors affecting health-seeking behaviour; and to qualitatively explore accessibility, availability, challenges and opportunities influencing compliance. Methods: A mixed-methods cross-sectional study was conducted at the non-communicable disease clinic of a tertiary care hospital in Surat, Gujarat, India from May to October 2023. The quantitative component included 300 adult hypertensive patients selected by convenient sampling. Data were collected using a semi-structured questionnaire capturing socio-demographic details, lifestyle practices, treatment characteristics, and the Hill-Bone compliance to high blood pressure therapy scale. The qualitative component comprised in-depth interviews with 10 hypertensive patients; thematic analysis was performed. Results: The mean±SD age of 300 participants was 56.8±10.7 years. Overall mean±SD for Hill Bone compliance score was 17.49±3.83 while those of medication compliance, sodium use and appointment keeping subscales were 9.38±2.22, 3.62±1.05 and 4.49±1.68 respectively. Only 61 (20.33%) participants were perfectly adherent according to Hill Bone compliance therapeutic scale while 239 (79.66%) participants were not. Qualitative themes included perceived severity of hypertension, financial constraints, health literacy, access barriers and the enabling role of family and counselling. Conclusions: Treatment compliance and health-seeking behaviour among hypertensive patients are influenced by an interplay of patient-related, therapy-related and system-level factors.